THE THE CORRELATION BETWEEN FORWARD HEAD POSTURE WITH STATIC BALANCE CONTROL OF STUDENT IN SMAN 1 SEMARAPURA - Puspitasari, Dewa Ayu; Wibawa, Ari; Primayanti, I Dewa Ayu Inten Dwi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Forward head posture is a posture problem which experienced by most school-age students. Forward head posture results in disproportion of postural muscles function. The aim of the study was to investigate the correlation between forward head posture with static balance control in which implemented a cross-sectional analytic design. The population of this study was students in age of 15-18 years old at SMAN 1 Semarapura. The participants were 84 students selected by using purposive sampling technique. Data were taken by Forward Head Test and One Leg Stance Test. The data of the test were analyzed by Spearman’s Rho Test with significance value p<0.05. The result showed that the best static balance control category mostly owned by normal head posture group (7 students). On the other hand, below average static balance control category mostly owned by forward head posture group (18 students). It was also founded the p value from the Spearman’s Rho Test was 0.004 (p<0.05) and the correlation coefficient value was 0,310. The conclusion there is a correlation between forward head posture with static balance control of students in SMAN 1 Semarapura. Keywords: forward head posture, static balance control